Novedoso profármaco derivado de la lilolidina con actividad dopaminérgica central. - Ramírez Morán, María Matilde; Angel Migliore, Ligia Biagina; Vera Sosa, Mariagracia; Velásquez Lugo, Marienmy del Valle; García Carmona, José Daniel; Salazar Castillo, Jesús Alberto; Villalba, Alejandra del Valle; Migliore, Biagina del Carmen; Charris Charris, Jaime; Israel, Anita; López D´Sola, Simón; Izquierdo, Rodolfo; et al. (Investigación Clínica, 2017)
Ver Resumen PDF.